EPIGENETIC STUDY AS A NEW APPROACH FOR THERAPEUTICS AND BIOMARKER OF ATHEROSCLEROSIS IN COVID-19 - Ferdianti, Fine N; Viradanti, Tersia; Utami, Sinta D (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction : Coronavirus disease 2019 (COVID-19) has affected more than 105 million people globally and resulted in at least 2.3 million deaths. Covid-19 has highlighted the vulnerability of aging populations to emerging diseases. This susceptibility to disease and death is also a major challenge for the development of vaccines and immunotherapeutic agents. Atherosclerosis is one of the main cardiovascular disease, and this disease is one of the most common comorbid diseases affected by Covid-19 and is associated with increased risk of mortality. Biomarker are crucial in decision-making in order to facilitate efficient resource allocation. Recently many researcher develop several biomarker as a new approach in epigenetic area. The discovery of new therapeutic targets as well as biomarkers using epigenetic studies may increase its clinical usefulness.Â Methods: In this narrative review, a search was carried out with the help of several search engines that match the criteria, namely